Systemic Functional Analysis of NATO’s Linguistic Strategies to Debunk Russian Information Warfare - Muhammad Andrean Syahsurya; Fariq Shiddiq Tasaufy (Prodi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam Darul Ulum Lamongan*, 2025)
Information warfare has become a vital area in modern geopolitical battles because language functions as both a combat tool and a defensive mechanism. The research investigates NATO's development of epistemic authority in counter-disinformation discourse through Systemic Functional Linguistics (SFL) analysis. The study analyzes NATO's